PENERAPAN SISTEM REKOMENDASI UKURAN CINCIN OTOMATIS UNTUK MENINGKATKAN EFISIENSI PRODUKSI DAN LAYANAN DI UMKM PERAK SIDEMEN SILVER CLASS - Ayu Manik Dirgayusari; Ni Kade Ayu Nirwana; Ketut Gde Manik Karvana; I Kadek Wira Dharma Prayana (ASOSIASI IDEBAHASA KEPRI, 2026)
Sidemen Silver Class is a prominent silver jewelry production house in Bali that offers two primary services: ready-made jewelry purchasing and custom ring crafting. The initial and critical step in custom ring making is finger size measurement. Currently, this process relies heavily on manual ring sizers through a trial-and-error approach. This conventional method is time-consuming, taking approximately one to five minutes per customer, which often leads to inefficiencies during peak hours. To address this issue, this study proposes an alternative solution by developing an automated ring size recommendation system utilizing an Arduino Uno and VL53L0X sensors. The system employs two opposing VL53L0X sensors to precisely measure the user's finger diameter. The captured diameter is then converted into international standard ring sizes using the circle circumference formula. Subsequently, a 16x2 I2C LCD displays the three closest size recommendations. This innovation is expected to significantly expedite the measurement process and improve operational efficiency at Sidemen Silver Class.